1295School age outcomes in IVF-conceived children compared with controls: a population linkage study. (2nd September 2021) - Kennedy, Amber; Vollenhoven, Beverley; Hiscock, Richard; Stern, Catharyn; Walker, Susan; Cheong, Jeanie; Quach, Jon; Hastie, Roxanne; Wilkinson, David; McBain, John; Gurrin, Lyle; MacLachlan, Vivien; et al.
Abstract: Background: There is interest in longer term outcomes in IVF-conceived offspring compared with those conceived naturally. So far, the findings have been conflicting. The Australian Early Developmental Consensus (AEDC) assesses children in their first year of primary school across five domains. Methods: To compare school entry outcomes in IVF-conceived children with naturally conceived controls, we undertook a statewide data linkage study, with perinatal data (2005-2014) linked to data from IVF providers in Victoria and the AEDC. Our approach to analysis included: complete case analysis, multiple imputation of missing data, consideration of clustering (siblings) and inverse probability weighted modeling to adjust for covariates. Our primary outcome was an AEDC score indicative of developmental vulnerability in two or more domains. We adjusted for confounders: child's age at assessment, sex, highest level of maternal education, maternal age, parity, SEIFA (Socio-Economic Indexes for Areas) quintile, language background other than English, and Aboriginal and Torres Strait Islander (ATSI) status. Results: The linked dataset comprised 163, 418 children, including 4, 441 IVF-conceived children. The IVF-conceived population had older, more highly educated mothers who lived in more affluent areas and were less likely to be from non-English speaking backgrounds or identify as ATSI. IVF-conceived children were less likely to be developmentally vulnerable, in both unadjusted (RR 0.59, 95%CI:0.52-0.67, p < 0.001) and adjusted analyses (aRR 0.72, 95%CI:0.58-0.88, p < 0.001). Conclusions: IVF-conceived were less likely to be developmentally vulnerable in their first year of schooling, compared with peers conceived naturally.